Polyvinyl alcohol composite fiber material, preparation method thereof and artificial heart valve device

The preparation of polyvinyl alcohol composite fiber materials through directional frozen casting, metal ion cross-linking and heat treatment has solved the problem of insufficient mechanical properties of hydrogel heart valve materials, and achieved the improvement of high strength and fatigue resistance, which is suitable for congenital heart disease Treatment of infants and young children.

CN119215227APending Publication Date: 2024-12-31INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411291528.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The mechanical properties of existing hydrogel heart valve materials are insufficient, and they lack directional fiber structure and fatigue resistance, making it difficult to be suitable for the treatment of infants and young children with congenital heart disease.

Method used

Using the preparation method of polyvinyl alcohol composite fiber material, polyvinyl alcohol composite fiber material with directional fiber structure is formed through directional frozen casting, metal ion cross-linking and heat treatment, to simulate the fiber structure and sponge layer of human tissue, and enhance the mechanics of the material. performance.

Benefits of technology

The tensile strength and fatigue resistance of polyvinyl alcohol composite fiber material are improved, making it suitable for artificial heart valves, simulate the mechanical anisotropy and porous structure of natural heart valves, and enhance the stability and durability of service in vivo.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215227A_ABST
    Figure CN119215227A_ABST
Patent Text Reader

Abstract

The invention relates to a polyvinyl alcohol composite fiber material, a preparation method thereof and an artificial heart valve device. The preparation method of the polyvinyl alcohol composite fiber material comprises the following steps: carrying out directional freezing casting treatment on a polyvinyl alcohol-based hydrogel solution, and replacing ice crystals to obtain hydrogel with a directional fiber structure; cross-linking groups on the hydrogel with the oriented fiber structure with metal ions to obtain the oriented fiber structure hydrogel with an ionic bond reinforced gel network; and carrying out heat treatment on the oriented fiber structure hydrogel with the ionic bond reinforced gel network to obtain the polyvinyl alcohol composite fiber material with a structure similar to the oriented fiber structure in human tissues. Wherein the polyvinyl alcohol composite fiber material is used as an artificial heart valve material. The preparation method is mainly used for preparing the polyvinyl alcohol composite fiber material, and the polyvinyl alcohol composite fiber material has a high-strength and oriented fiber structure, so that the polyvinyl alcohol composite fiber material can be used as an artificial heart valve material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a polyvinyl alcohol composite fiber material and a preparation method thereof, and an artificial heart valve device. Background Art

[0002] The number of patients with congenital heart disease worldwide is as high as 13 million, and more than 210,000 people die from it. Unlike adults, infants and young children with congenital heart valve disease are more difficult to treat. At present, the commonly used artificial heart valves in clinical practice are mechanical valves and biological valves, but due to the lack of tissue remodeling and regeneration functions, these two types of valves cannot be used to treat infants and young children with congenital heart disease. In contrast, tissue-engineered valves with tissue remodeling and regeneration functions have significant advantages in the treatment of congenital heart valve diseases. They are constructed by using cell scaffolds, seed cells, and active factors, and the main cell scaffold material must have good biocompatibility to promote cell growth and tissue regeneration.

[0003] Hydrogel is a hydrophilic polymer material with adjustable physical and chemical properties. By adjusting the composition ratio and cross-linking method, it can show different shapes and functions, presenting a three-dimensional porous structure, similar to the natural extracellular matrix structure, and has good biocompatibility. At present, the main problem restricting the development of hydrogel valves is the poor mechanical properties of the hydrogel itself. For example, the tensile strength of the hydrogel valve cross-linked by hydrogen bonds is only 2.08MPa, and it lacks the anisotropic fiber structure characteristics similar to natural heart valves. At the same time, the long-term complex service environment in the body also puts higher requirements on the tear resistance and fatigue resistance of hydrogel materials.

[0004] In summary, there is an urgent need to design a high-strength hydrogel material with a directional fiber structure similar to that in human tissue to serve as an artificial heart valve material. Summary of the invention

[0005] In view of this, the present invention provides a polyvinyl alcohol composite fiber material and a preparation method thereof, and an artificial heart valve device. The main purpose is to prepare a high-strength polyvinyl alcohol composite fiber material with a directional fiber structure, which can be used as an artificial heart valve material.

[0006] In order to achieve the above object, the present invention mainly provides the following technical solutions:

[0007] On the one hand, an embodiment of the present invention provides a method for preparing a polyvinyl alcohol composite fiber material, which comprises the following steps:

[0008] Directed freeze casting step: performing a directed freeze casting process on the polyvinyl alcohol-based hydrogel solution to obtain a hydrogel with a directed fiber structure after replacing ice crystals;

[0009] Metal ion cross-linking step: cross-linking the groups on the hydrogel having an oriented fiber structure with metal ions, so as to realize cross-linking of the gel network through ionic bonds, thereby obtaining an oriented fiber structure hydrogel having an ionic bond-reinforced gel network;

[0010] Heat treatment step: heat-treating the oriented fiber structure hydrogel with ionic bond reinforced gel network to obtain a polyvinyl alcohol composite fiber material with an oriented fiber structure similar to that in human tissue.

[0011] Preferably, in the polyvinyl alcohol-based hydrogel solution, the mass fraction of polyvinyl alcohol is 5 to 30 wt %, preferably 5 to 15 wt %.

[0012] Preferably, the polyvinyl alcohol-based hydrogel solution further comprises one or more of gelatin, carboxymethyl chitosan and hyaluronic acid; preferably, when the polyvinyl alcohol-based hydrogel solution further comprises gelatin, the mass fraction of gelatin is 1 to 5wt%; preferably, when the polyvinyl alcohol-based hydrogel solution further comprises carboxymethyl chitosan, the mass fraction of carboxymethyl chitosan is 1 to 3wt%; preferably, when the polyvinyl alcohol-based hydrogel solution further comprises hyaluronic acid, the mass fraction of hyaluronic acid is 1 to 5wt%.

[0013] Preferably, in the directional freeze-casting step: the polyvinyl alcohol-based hydrogel solution is placed in a mold for directional freeze-casting treatment; preferably, the bottom surface of the mold is placed on a cold table of a directional freezing device for directional freeze-casting treatment; and / or the temperature of the directional freeze-casting treatment is -40 to -90°C, and the time of the directional freeze-casting treatment is 1 to 6 hours; and / or the gel after the directional freeze-casting treatment is immersed in anhydrous ethanol to replace ice crystals and retain the directional fiber structure to obtain a hydrogel with an directional fiber structure; and / or the temperature of replacing ice crystals is -15 to -20°C, and the duration of replacing ice crystals is 12 to 48 hours, preferably 36 to 48 hours.

[0014] Preferably, in the directional freeze-casting step: the gel network in the hydrogel with an directional fiber structure is cross-linked by polyvinyl alcohol through intermolecular and intramolecular hydrogen bonds; preferably, the gel network in the hydrogel with an directional fiber structure is cross-linked by polyvinyl alcohol and active additives through intermolecular and intramolecular hydrogen bonds; wherein the active additives include one or more of gelatin, carboxymethyl chitosan, and hyaluronic acid; and / or during the directional freeze-casting treatment, the hydrogel self-assembles under the action of directionally growing ice crystals to form an directional fiber structure and exists stably.

[0015] Preferably, in the metal ion cross-linking step: the metal ion is Fe 3+ 、Al 3+, Ca 2+ , Cu 2+ One or more of the above; and / or cross-linking the hydroxyl groups and carboxyl groups on the hydrogel having an oriented fiber structure with metal ions to obtain an oriented fiber structure hydrogel having an ion bond-reinforced gel network; and / or pre-cooling the metal ion solution at -10 to -20°C for 10 to 20 hours; maintaining the condition of -10 to -20°C, soaking the hydrogel having an oriented fiber structure in the pre-cooled metal ion solution for 12 to 48 hours to cross-link the groups on the hydrogel having an oriented fiber structure with the metal ions; preferably, the ion concentration of the metal ion solution is 0.05 to 0.1 M; preferably, the metal ion solution is an anhydrous ethanol solution of metal ions.

[0016] Preferably, in the heat treatment step: the heat treatment temperature is 50 to 120° C., and the heat treatment time is 6 to 48 hours.

[0017] Preferably, before the heat treatment step, the oriented structure hydrogel having an ionically reinforced gel network needs to be cleaned to remove the uncrosslinked metal ions.

[0018] On the other hand, an embodiment of the present invention provides a polyvinyl alcohol composite fiber material, wherein the polyvinyl alcohol composite fiber material is a directional fiber structure; wherein the gel network of the polyvinyl alcohol composite fiber material is assembled by hydrogen bonds, ionic bond crosslinking, and hydrogel molecular chain entanglement; preferably, the width of the directional fiber structure in the polyvinyl alcohol composite fiber material is 5-50μm; preferably, the polyvinyl alcohol composite fiber material is a porous structure with a pore size of 1-5μm in a completely dry state; preferably, the polyvinyl alcohol composite fiber material is prepared by the preparation method of the polyvinyl alcohol composite fiber material described in any one of the above.

[0019] On the other hand, an embodiment of the present invention further provides an artificial heart valve device, wherein the artificial heart valve device includes an artificial heart valve, wherein the material of the artificial heart valve is the above-mentioned polyvinyl alcohol composite fiber material.

[0020] Compared with the prior art, the polyvinyl alcohol composite fiber material and its preparation method, and the artificial heart valve device of the present invention have at least the following beneficial effects:

[0021] The embodiment of the present invention adopts a method of directional freezing casting to prepare a hydrogel with an oriented fiber structure; then, the groups on the hydrogel with an oriented fiber structure are cross-linked with metal ions to strengthen the gel network through ionic cross-linking, thereby obtaining an oriented fiber structure hydrogel with an ionic reinforced gel network; the oriented fiber structure hydrogel with an ionic reinforced gel network is heat-treated to achieve the degree of entanglement of the gel network molecular chains, further strengthening the gel network, and obtaining a polyvinyl alcohol composite fiber material. Here, by the above method, the prepared polyvinyl alcohol composite fiber material has an oriented fiber structure (i.e., similar to the oriented fiber structure in human tissue), and its strength comes from the oriented fiber structure and the strengthened gel network inside it (the gel network is formed by hydrogen bonds, ionic cross-linking and entanglement of hydrogel molecular chains). Here, when the polyvinyl alcohol composite fiber material is used for artificial heart valve materials, the oriented fiber structure simulates the orientation arrangement of collagen fibers of natural heart valves and has mechanical anisotropy. Its inherent porous structure simulates the sponge layer of natural heart valves and can be used as a buffer layer in the in vivo service environment to allow shear and deformation caused by valve opening and closing. In addition, this oriented fiber structure can also inhibit crack propagation and improve the fatigue resistance of artificial heart valves during service.

[0022] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A flow chart for preparing a polyvinyl alcohol composite fiber material provided by an embodiment of the present invention;

[0024] Figure 2 This is a microscopic morphology of the hydrogel prepared in Example 1; wherein, Figure 2 Figure (a) is a microscopic morphology of a hydrogel (PGC hydrogel) with an oriented fiber structure prepared by oriented freeze casting in Example 1, Figure (b) is an enlarged view of the box in Figure (a), Figure (c) is a microscopic morphology of a hydrogel (PGC / Fe) with an ionically reinforced gel network prepared by immersion in anhydrous ferric chloride ethanol solution in Example 1, Figure (d) is an enlarged view of the box in Figure (c), Figure (e) is a microscopic morphology of a polyvinyl alcohol composite fiber material (aPGC / Fe) prepared after heat treatment in Example 1, and Figure (f) is an enlarged view of the box in Figure (e);

[0025] Figure 3The composition and structure characterization diagrams of PGC and PGC / Fe in Example 1; wherein (a) is a FITR characterization diagram of PGC and PGC / Fe, and (b) is an XRD characterization diagram of PGC and PGC / Fe;

[0026] Figure 4 The mechanical anisotropy characterization diagram of the polyvinyl alcohol composite fiber material (aPGC / Fe) prepared in Example 1; wherein (a) is a tensile stress-strain curve parallel to the directional freezing direction (Y) and perpendicular to the directional freezing direction (X), and (b) is a tensile strength and elastic modulus in the Y and X directions;

[0027] Figure 5 The mechanical properties of the polyvinyl alcohol composite fiber material (aPGC / Fe) prepared in Example 2 are characterized; wherein (a) is the tensile stress-strain curve of the polyvinyl alcohol composite fiber material (aPGC / Fe) after being treated with 0.05M and 0.1M ferric chloride anhydrous ethanol solutions, and (b) is the tensile strength and elastic modulus of the polyvinyl alcohol composite fiber material (aPGC / Fe) after being treated with 0.05M and 0.1M ferric chloride anhydrous ethanol solutions;

[0028] Figure 6 The mechanical properties of the polyvinyl alcohol composite fiber material (aPGC / Fe) prepared in Example 3 are characterized; wherein (a) is the tensile stress-strain curve of the polyvinyl alcohol composite fiber material (aPGC / Fe) heat-treated for 24h and 48h, and (b) is the tensile strength and elastic modulus of the polyvinyl alcohol composite fiber material (aPGC / Fe) heat-treated for 24h and 48h;

[0029] Figure 7 The cytotoxicity characterization diagram of PGC, PGC / Fe and aPGC / Fe prepared in Example 1;

[0030] Figure 8 Figure 1 shows the fluid dynamics detection curve of the artificial heart valve device made of the polyvinyl alcohol composite fiber material (aPGC / Fe) prepared in Example 1, (a) shows the curve of aortic pressure, ventricular pressure and fluid flow rate changing with time, (b) shows the image of the valve when it is opened and closed. DETAILED DESCRIPTION

[0031] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention application are described in detail below in conjunction with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.

[0032] The present invention is mainly used to design a high-strength polyvinyl alcohol composite fiber material with a directional fiber structure, which effectively strengthens the mechanical properties of the material, improves the service performance of the material and greatly prolongs its service life. It has the potential to be used as an alternative material for artificial heart valves.

[0033] The present invention adopts a directional freezing casting method to prepare a hydrogel with an oriented fiber structure, in which a polyvinyl alcohol-based hydrogel solution is subjected to directional freezing to obtain a hydrogel with an oriented fiber structure. Then, an ion network is constructed inside the hydrogel by soaking in an anhydrous ethanol solution containing metal ions. Specifically, the hydrogel with an oriented structure is placed in an anhydrous ethanol solution containing metal ions, and ionic bonds are formed by combining the metal ions with -OH and -COOH on the hydrogel molecular chain, thereby obtaining a high-strength ion network. Finally, the degree of entanglement of the gel network molecular chain is achieved through a heat treatment process, and the gel network is further strengthened, and finally dehydration and assembly are performed to obtain an oriented fiber structure. The specific scheme of the present invention is as follows:

[0034] On the one hand, the present invention provides a method for preparing a polyvinyl alcohol composite fiber material, such as Figure 1 As shown, it includes the following steps:

[0035] Hydrogel solution preparation steps: prepare a polyvinyl alcohol-based hydrogel solution.

[0036] Preferably, in the polyvinyl alcohol-based hydrogel solution, the mass fraction of polyvinyl alcohol is 5 to 30 wt %, preferably 5 to 15 wt %. Preferably, the preparation temperature is 80 to 90° C. for rapid and uniform dissolution.

[0037] The polyvinyl alcohol-based hydrogel solution further comprises one or more of gelatin (Gel), carboxymethyl chitosan (CMCS), and hyaluronic acid (HA); when the polyvinyl alcohol-based hydrogel solution further comprises gelatin, the mass fraction of gelatin is 1 to 5 wt%, and the preparation temperature is 40 to 55° C. to avoid gelatin denaturation; when the polyvinyl alcohol-based hydrogel solution further comprises carboxymethyl chitosan, the mass fraction of carboxymethyl chitosan is 1 to 3 wt%; when the polyvinyl alcohol-based hydrogel solution further comprises hyaluronic acid, the mass fraction of hyaluronic acid is 1 to 5 wt%. Here, by adding one or more of gelatin (Gel), carboxymethyl chitosan (CMCS), and hyaluronic acid (HA) to the polyvinyl alcohol-based hydrogel solution, it is helpful to improve the cross-linking activity.

[0038] Directed freeze casting step: subjecting the polyvinyl alcohol-based hydrogel solution to a directed freeze casting treatment to obtain a hydrogel with a directed fiber structure after replacing ice crystals; wherein, in the polyvinyl alcohol-based hydrogel solution, the mass fraction of polyvinyl alcohol is 5 to 30 wt%.

[0039] In this step, a polyvinyl alcohol-based hydrogel solution is poured into a mold and subjected to directional freeze casting, and then the material is taken out and immersed in anhydrous ethanol to replace ice crystals while retaining the obtained directional structure to obtain a hydrogel with a directional fiber structure.

[0040] Preferably, the polyvinyl alcohol-based hydrogel solution is poured into a mold with a length × width × height = (30-100 mm × (0.3-0.6 mm × (30-100 mm), and the bottom surface (the surface where the length × width is located) is placed on a cold table of a directional freezing device, and the cold table is cooled to -40 to -90°C. After 1 to 6 hours of directional freezing casting, it is taken out of the mold.

[0041] Preferably, the temperature of replacing ice crystals is -15 to -20°C, and the duration is 12 to 48 hours.

[0042] Metal ion cross-linking step: cross-linking the groups on the hydrogel with oriented fiber structure with metal ions, so that the gel network is cross-linked through ionic bonds to obtain an oriented fiber structure hydrogel with an ionic bond-reinforced gel network.

[0043] In this step, the gel network in the oriented fiber structure is strengthened by ionic cross-linking, specifically, by cross-linking of metal ions with hydroxyl (-OH) and carboxyl (-COOH) groups on the hydrogel molecular chains. The specific steps are: preparing an anhydrous ethanol solution containing metal ions, and precooling it at -10 to -20°C for 10 to 20 hours; then, maintaining the condition of -10 to -20°C, immersing the hydrogel with an oriented fiber structure in the anhydrous ethanol solution containing metal ions for 12 to 48 hours.

[0044] Preferably, the metal ion is Fe 3+ 、Al 3+ , Ca 2+ , Cu 2+ One or more of .

[0045] Preferably, the metal ion concentration in the anhydrous ethanol solution of metal ions is 0.05-0.1M.

[0046] Heat treatment step: heat-treating the oriented fiber structure hydrogel with ionic bond reinforced gel network to obtain a polyvinyl alcohol composite fiber material with an oriented fiber structure similar to that in human tissue.

[0047] In this step, heat treatment is used to further achieve the degree of entanglement of the gel network molecular chains, thereby strengthening the gel network, and finally dehydration and assembly are performed to obtain a directional fiber structure.

[0048] The heat treatment temperature is 50-120° C., and the heat treatment time is 6-48 hours.

[0049] On the other hand, an embodiment of the present invention provides a polyvinyl alcohol composite fiber material, wherein the polyvinyl alcohol composite fiber material is a oriented fiber structure; the oriented fiber structure is prepared by a oriented freeze-casting method, and its high strength originates from the oriented fiber structure and the reinforced gel network inside it, and the gel network is formed by hydrogen bonds, ionic bonds cross-linking and entanglement of hydrogel molecular chains.

[0050] On the other hand, an embodiment of the present invention provides an application of a polyvinyl alcohol composite fiber material as or in the preparation of an artificial heart valve material. Here, when the polyvinyl alcohol composite fiber material is used for an artificial heart valve, the oriented fiber structure simulates the oriented arrangement of collagen fibers of a natural heart valve, has mechanical anisotropy, and its inherent porous structure simulates the sponge layer of a natural heart valve, which can be used as a buffer layer in the in vivo service environment, allowing shear and deformation caused by the opening and closing of the valve. In addition, this oriented network structure can also inhibit crack propagation and improve the fatigue resistance of the artificial heart valve during service.

[0051] The present invention is further described below by specific embodiments:

[0052] Example 1

[0053] This embodiment prepares a polyvinyl alcohol composite fiber material and an artificial heart valve device, and the main steps are as follows:

[0054] 1) Preparation of hydrogel solution: 6 g of polyvinyl alcohol (PVA) was weighed and placed in 50 mL of deionized water, and stirred at 500 rpm for 1 h in a water bath at 90° C. to obtain a uniform aqueous solution, then cooled to 55° C., 1.8 g of gelatin (Gel) and 1.2 g of carboxymethyl chitosan (CMCS) were added to the solution and stirred for 1 h to obtain a uniform mixed solution (polyvinyl alcohol-based hydrogel solution). In the polyvinyl alcohol-based hydrogel solution, the concentrations of PVA, Gel and CMCS were 10 wt%, 3 wt% and 2 wt%, respectively.

[0055] 2) Directed freezing casting step: Pour the hydrogel solution into a mold with a thickness of 600 μm (length × width × height = 50 mm × 0.6 mm × 500 mm), place the bottom surface (length × width surface) on the cold stage of the directional freezing device, cool the cold stage to -80°C, and apply a temperature gradient from bottom to top to the hydrogel. At the same time, to avoid the influence of external temperature, wrap the outside of the mold with a heat preservation cloth. After directional freezing casting for 2 hours, take it out of the mold.

[0056] The material was taken out of the mold and immersed in anhydrous ethanol at -16°C for 48 hours. The icicles (ice crystals) grown in the hydrogel were replaced by anhydrous ethanol, thereby retaining the oriented fiber structure and obtaining a hydrogel with an oriented fiber structure (PGC). The microscopic morphology is shown in Figure 2From Figure (a) and Figure (b), it can be seen that it has an obvious oriented fiber structure.

[0057] 3) Metal ion cross-linking step:

[0058] Weigh 5.4 g of ferric chloride hexahydrate (FeCl3·6H2O), put it into 200 mL of anhydrous ethanol, and ultrasonicate it for 10 min to fully dissolve it. Prepare an anhydrous ethanol solution of ferric chloride with a concentration of 0.1 M, and put it in a refrigerator at -16°C for precooling for 12 h.

[0059] The hydrogel with oriented fiber structure (PGC) was placed in anhydrous ethanol solution of ferric chloride and continued to be immersed at -16°C for 48h to obtain an oriented fiber structure hydrogel (PGC / Fe) with an ion bond-reinforced gel network. Figure 2 As shown in Figure (c) and Figure (d), it has a clear oriented fiber structure, such as Figure 3 As shown in Figure (a), after being treated with anhydrous ethanol solution of ferric chloride, the characteristic peaks of -OH and -COOH on the molecular chains of PVA, Gel, and CMCS shifted, proving that Fe 3+ and - OH and - COOH forms an ionic bond.

[0060] 4) Heat treatment: The oriented fiber structure hydrogel (PGC / Fe) with ion bond reinforced gel network was immersed in anhydrous ethanol for 24 h, and the liquid was replaced every 8 h. Then, the PGC / Fe was taken out and the excess Fe was washed off. 3+ After being dried with filter paper, the obtained product was placed in an electric hot air drying oven and heat treated at 60°C for 48h to obtain a polyvinyl alcohol composite fiber material (aPGC / Fe). Figure 2 As shown in Figures (e) and (f), the width of the oriented fiber structure is about 20 μm. The polyvinyl alcohol composite fiber material (aPGC / Fe) has a porous structure with a pore size of about 1 to 5 μm. Figure 3 As shown in Figure (b), the polyvinyl alcohol composite fiber material (aPGC / Fe) has an obvious crystallization peak, indicating that heat treatment promotes the entanglement of hydrogel molecular chains.

[0061] Figure 4 The mechanical anisotropy characterization diagram of the polyvinyl alcohol composite fiber material (aPGC / Fe) prepared in Example 1; wherein (a) is the tensile stress-strain curve parallel to the directional freezing direction (Y) and perpendicular to the directional freezing direction (X), and (b) is the tensile strength and elastic modulus in the Y and X directions. Figure 4It can be seen that the tensile strength of aPGC / Fe hydrogel in the X direction is low, only 1.13MPa, while the tensile strength in the Y direction reaches 5.03MPa. Similarly, the elastic modulus in the X direction is only 3.18MPa, while the elastic modulus in the Y direction increases to 8.16MPa. Its anisotropy ratio is similar to that of natural heart valves.

[0062] Figure 7 This is a cytotoxicity characterization diagram of PGC, PGC / Fe and aPGC / Fe prepared in Example 1; it can be seen that the three hydrogels, PGC, PGC / Fe and aPGC / Fe, have no obvious cytotoxicity.

[0063] 5) Using the polyvinyl alcohol composite fiber material (aPGC / Fe) prepared above as an artificial heart valve material to prepare an artificial heart valve device.

[0064] Figure 8 Figure 1 shows the fluid dynamics detection curve of the artificial heart valve device made of the polyvinyl alcohol composite fiber material (aPGC / Fe) prepared in Example 1, (a) shows the curve of aortic pressure, ventricular pressure and fluid flow rate changing with time, (b) shows the image of the valve when it is opened and closed.

[0065] The calculated regurgitation ratio of the artificial heart valve device is 4.7%, and the effective opening area is 2.4 cm 2 The results show that it has lower energy loss, and the regurgitation ratio and effective opening area of ​​the valve meet the ISO 5840-2 standard (for surgical valves with an inner diameter of 23 mm, the effective opening area is ≥1.45 cm 2 and the reflux ratio ≤15%).

[0066] Example 2

[0067] This embodiment prepares a polyvinyl alcohol composite fiber material, and the main steps are as follows:

[0068] 1) Preparation of hydrogel solution: 6 g of polyvinyl alcohol (PVA) was weighed and put into 50 mL of deionized water, and stirred at 500 rpm for 1 h in a water bath at 90° C. to obtain a uniform aqueous solution, then cooled to 55° C., 1.8 g of gelatin (Gel) and 1.2 g of carboxymethyl chitosan (CMCS) were added to the solution and stirred for 1 h to obtain a uniform mixed solution (polyvinyl alcohol-based hydrogel solution). In the polyvinyl alcohol-based hydrogel solution, the concentrations of PVA, Gel and CMCS were 10 wt%, 3 wt% and 2 wt%, respectively.

[0069] 2) Directed freezing casting step: Pour the hydrogel solution into a mold with a thickness of 600 μm (length × width × height = 400 mm × 0.6 mm × 400 mm), place the bottom surface (length × width surface) on the cold stage of the directional freezing device, cool the cold stage to -80°C, and apply a temperature gradient from bottom to top to the hydrogel. At the same time, to avoid the influence of external temperature, wrap the outside of the mold with a heat preservation cloth. After directional freezing casting for 2 hours, take it out of the mold.

[0070] The material was taken out of the mold and immersed in anhydrous ethanol at -16°C for 48 hours. Anhydrous ethanol was used to replace the icicles (ice crystals) grown in a directional manner in the hydrogel, thereby retaining the directional fiber structure and obtaining a hydrogel (PGC) with a directional fiber structure.

[0071] 3) Metal ion cross-linking step:

[0072] Weigh 2.7 g of ferric chloride hexahydrate (FeCl3·6H2O) and 5.4 g of ferric chloride hexahydrate (FeCl3·6H2O), respectively, put them into 200 mL of anhydrous ethanol, ultrasonicate for 10 min to fully dissolve them, prepare anhydrous ethanol solutions of ferric chloride with concentrations of 0.05 M and 0.1 M, respectively, and precool them in a -16°C refrigerator for 12 h.

[0073] The hydrogel with oriented fiber structure (PGC) was placed in ferric chloride anhydrous ethanol solutions of different concentrations and continued to be immersed at -16°C for 48 hours to obtain oriented fiber structure hydrogel (PGC / Fe) with ion bond reinforced gel network.

[0074] 4) Heat treatment: The oriented fiber structure hydrogel (PGC / Fe) with ionic bond-reinforced gel network was immersed in anhydrous ethanol for 24 h, and the liquid was replaced every 8 h. Then, the PGC / Fe was taken out and the excess Fe was washed off. 3+ After being wiped dry with filter paper, it was placed in an electric hot air drying oven and heat treated at 60°C for 48h to obtain a polyvinyl alcohol composite fiber material (aPGC / Fe).

[0075] Figure 5The mechanical properties of the polyvinyl alcohol composite fiber material (aPGC / Fe) prepared in Example 2 are characterized; wherein (a) shows the tensile stress-strain curve of the polyvinyl alcohol composite fiber material (aPGC / Fe) after being treated with 0.05M and 0.1M ferric chloride anhydrous ethanol solutions, and (b) shows the tensile strength and elastic modulus of the polyvinyl alcohol composite fiber material (aPGC / Fe) after being treated with 0.05M and 0.1M ferric chloride anhydrous ethanol solutions. It can be seen that due to the formation of more ionic bonds, the mechanical properties of the aPGC / Fe composite fiber material treated with 0.1M ferric chloride anhydrous ethanol solution are significantly improved, with the tensile strength increasing from 1.39MPa to 5.03MPa, and the elastic modulus increasing from 2.22MPa to 8.16MPa.

[0076] Example 3

[0077] This embodiment prepares a polyvinyl alcohol composite fiber material, and the main steps are as follows:

[0078] 1) Preparation of hydrogel solution: 6 g of polyvinyl alcohol (PVA) was weighed and put into 50 mL of deionized water, and stirred at 500 rpm for 1 h in a water bath at 90° C. to obtain a uniform aqueous solution, then cooled to 55° C., 1.8 g of gelatin (Gel) and 1.2 g of carboxymethyl chitosan (CMCS) were added to the solution and stirred for 1 h to obtain a uniform mixed solution (polyvinyl alcohol-based hydrogel solution). In the polyvinyl alcohol-based hydrogel solution, the concentrations of PVA, Gel and CMCS were 10 wt%, 3 wt% and 2 wt%, respectively.

[0079] 2) Directed freezing casting step: Pour the hydrogel solution into a mold with a thickness of 600 μm (length × width × height = 450 mm × 0.6 mm × 450 mm), place the bottom surface (length × width surface) on the cold stage of the directional freezing device, cool the cold stage to -80°C, and apply a temperature gradient from bottom to top to the hydrogel. At the same time, to avoid the influence of external temperature, wrap the outside of the mold with a heat preservation cloth. After directional freezing casting for 2 hours, take it out of the mold.

[0080] The material was taken out of the mold and immersed in anhydrous ethanol at -16°C for 48 hours. Anhydrous ethanol was used to replace the icicles (ice crystals) grown in a directional manner in the hydrogel, thereby retaining the directional fiber structure and obtaining a hydrogel (PGC) with a directional fiber structure.

[0081] 3) Metal ion cross-linking step:

[0082] Weigh 5.4 g of ferric chloride hexahydrate (FeCl3·6H2O), put it into 200 mL of anhydrous ethanol, and ultrasonicate it for 10 min to fully dissolve it. Prepare an anhydrous ethanol solution of ferric chloride with a concentration of 0.1 M, and put it in a refrigerator at -16°C for precooling for 12 h.

[0083] The hydrogel with oriented fiber structure (PGC) was placed in anhydrous ethanol solution of ferric chloride and continued to be immersed at a temperature of -16°C for 48 hours to obtain an oriented fiber structure hydrogel (PGC / Fe) with an ion bond reinforced gel network.

[0084] 4) Heat treatment: The oriented fiber structure hydrogel (PGC / Fe) with ionic bond-reinforced gel network was immersed in anhydrous ethanol for 24 h, and the liquid was replaced every 8 h. Then, the PGC / Fe was taken out and the excess Fe was washed off. 3+ After being dried with filter paper, the samples were divided into two groups and placed in an electric forced air drying oven. They were heat treated at 60°C for different time periods (one group was heat treated for 24 h and the other group was heat treated for 48 h) to obtain polyvinyl alcohol composite fiber materials (aPGC / Fe).

[0085] Figure 6 The mechanical properties of the polyvinyl alcohol composite fiber material (aPGC / Fe) prepared in Example 3 are characterized; wherein (a) is the tensile stress-strain curve of the polyvinyl alcohol composite fiber material (aPGC / Fe) after 24h and 48h heat treatment, and (b) is the tensile strength and elastic modulus of the polyvinyl alcohol composite fiber material (aPGC / Fe) after 24h and 48h heat treatment. It can be seen that the longer the heat treatment time, the more obvious the promotion effect on the entanglement of the hydrogel molecular chain, so the mechanical properties are improved, the tensile strength increases from 1.76MPa to 5.03MPa, and the elastic modulus increases from 3.3MPa to 8.16MPa.

[0086] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a polyvinyl alcohol composite fiber material, characterized in that: It includes the following steps: Directed freeze casting step: performing a directed freeze casting process on the polyvinyl alcohol-based hydrogel solution to obtain a hydrogel with a directed fiber structure after replacing ice crystals; Metal ion cross-linking step: cross-linking the groups on the hydrogel having an oriented fiber structure with metal ions, so as to realize cross-linking of the gel network through ionic bonds, thereby obtaining an oriented fiber structure hydrogel having an ionic bond-reinforced gel network; Heat treatment step: heat-treating the oriented fiber structure hydrogel with ionic bond reinforced gel network to obtain a polyvinyl alcohol composite fiber material with an oriented fiber structure similar to that in human tissue.

2. The method for preparing a polyvinyl alcohol composite fiber material according to claim 1, characterized in that: In the polyvinyl alcohol-based hydrogel solution, the mass fraction of polyvinyl alcohol is 5 to 30 wt %, preferably 5 to 15 wt %.

3. The method for preparing the polyvinyl alcohol composite material according to claim 1 or 2, characterized in that: The polyvinyl alcohol-based hydrogel solution further contains one or more of gelatin, carboxymethyl chitosan, and hyaluronic acid; Preferably, when the polyvinyl alcohol-based hydrogel solution further contains gelatin, the mass fraction of gelatin is 1 to 5 wt %; Preferably, when the polyvinyl alcohol-based hydrogel solution further contains carboxymethyl chitosan, the mass fraction of the carboxymethyl chitosan is 1 to 3 wt %; Preferably, when the polyvinyl alcohol-based hydrogel solution further contains hyaluronic acid, the mass fraction of the hyaluronic acid is 1 to 5 wt %.

4. The method for preparing a polyvinyl alcohol composite fiber material according to any one of claims 1 to 3, characterized in that: In the directional freeze casting step: placing the polyvinyl alcohol-based hydrogel solution into a mold for directional freeze casting; preferably, placing the bottom surface of the mold on a cold stage of a directional freezing device for directional freeze casting; and / or The temperature of the directional freeze casting treatment is -40 to -90°C, and the time of the directional freeze casting treatment is 1 to 6 hours; and / or Soaking the gel after the oriented freeze casting process in anhydrous ethanol to replace ice crystals and retain the oriented fiber structure to obtain a hydrogel with an oriented fiber structure; and / or The temperature for replacing ice crystals is -15 to -20°C, and the duration for replacing ice crystals is 12 to 48 hours, preferably 36 to 48 hours.

5. The method for preparing the polyvinyl alcohol composite fiber material according to any one of claims 1 to 4, characterized in that: In the directional freeze casting step: The gel network in the hydrogel with oriented fiber structure is formed by cross-linking polyvinyl alcohol through intermolecular and intramolecular hydrogen bonds; preferably, the gel network in the hydrogel with oriented fiber structure is formed by cross-linking polyvinyl alcohol and active additives through intermolecular and intramolecular hydrogen bonds; wherein the active additives include one or more of gelatin, carboxymethyl chitosan, and hyaluronic acid; and / or During the directional freeze casting process, the hydrogel self-assembles under the action of the directional growing ice crystals to form a directional fiber structure and exists stably.

6. The method for preparing a polyvinyl alcohol composite fiber material according to any one of claims 1 to 5, characterized in that: In the metal ion cross-linking step: The metal ion is Fe 3+ 、Al 3+ , Ca 2+ , Cu 2+ One or more of; and / or Cross-linking the hydroxyl groups and carboxyl groups on the hydrogel having an oriented fiber structure with metal ions to obtain an oriented fiber structure hydrogel having an ion bond-reinforced gel network; and / or The metal ion solution is precooled at -10 to -20°C for 10 to 20 hours; the hydrogel with an oriented fiber structure is immersed in the precooled metal ion solution for 12 to 48 hours while maintaining the temperature at -10 to -20°C, so that the groups on the hydrogel with an oriented fiber structure are cross-linked with the metal ions; preferably, the ion concentration of the metal ion solution is 0.05 to 0.1 M; preferably, the metal ion solution is an anhydrous ethanol solution of metal ions.

7. The method for preparing a polyvinyl alcohol composite fiber material according to any one of claims 1 to 6, characterized in that: In the heat treatment step: the heat treatment temperature is 50 to 120° C., and the heat treatment time is 6 to 48 hours; and / or Before the heat treatment step, the oriented structure hydrogel having an ionically reinforced gel network needs to be cleaned to remove the uncrosslinked metal ions.

8. A polyvinyl alcohol composite fiber material, characterized in that: The polyvinyl alcohol composite fiber material is a directional fiber structure; wherein the gel network of the polyvinyl alcohol composite fiber material is assembled by hydrogen bonding, ionic bonding cross-linking, and hydrogel molecular chain entanglement; Preferably, the width of the oriented fiber structure in the polyvinyl alcohol composite fiber material is 5-50 μm; Preferably, the polyvinyl alcohol composite fiber material has a porous structure, and the pore size in a completely dry state is 1-5 μm; Preferably, the polyvinyl alcohol composite fiber material is prepared by the method for preparing the polyvinyl alcohol composite fiber material according to any one of claims 1-7.

9. Use of the polyvinyl alcohol composite fiber material according to claim 8 as or in the preparation of artificial heart valve materials.

10. An artificial heart valve device, characterized in that: The artificial heart valve device includes an artificial heart valve, wherein the material of the artificial heart valve is the polyvinyl alcohol composite fiber material according to claim 8.